THE INFLUENCE OF FINANCIAL TECHNOLOGY AND LIQUIDITY ON THE FINANCIAL PERFORMANCE OF BANKS IN INDONESIA - Salsabilla, Tata Agtya; Imronuddin, Imronuddin (Jurnal Comparative: Ekonomi dan Bisnis, 2024)
The purpose of this study is to evaluate how financial technology and liquidity levels affect the financial performance in conventional commercial banks in Indonesia that are listed in the Financial Services Authority. The research population includes conventional commercial banks listed on the Indonesia Stock Exchange from 2017 to 2023. The sampling technique is conducted through purposive sampling. The data analysis method uses panel data regression analysis. The data used are from 49 banks with a total of 176 financial reports, and hypothesis analysis is conducted using SPSS software. The research results indicate that financial technology has an impact on the financial performance of the banking sector in Indonesia, while liquidity levels also play a role in influencing the financial performance in the same banking sector.